The Genetic Polymorphism Relationship of GDF9 Gene Mutations to Milk Production and its Components in Awassi Sheep - Hussein Ali Hussein,; Hadi Awad Hassooni, (American Journal of Biology and Natural Sciences, 2025)
The study was conducted on 67 ewes and their offspring at the Khairat Al-Ittihad Sheep and Cattle Breeding Station in Babil Governorate, Iraq, from December 2023 to May 2024. Data were collected from the station's records, including ages, weights, and birth sequences, as well as laboratory analyses of blood and milk samples. This study aimed to investigate the genetic polymorphism of GDF9 gene mutations with milk production and milk components in Awassi sheep. DNA was extracted from blood samples using specialized techniques, and the target genes GDF9 and PRL were amplified using polymerase chain reaction (PCR). The results showed no nucleotide changes (mutations) in the GDF9 gene, while three mutations were identified in the PRL gene: SNP1: 277 C>T, SNP2: 684 G>T, and SNP3: 737 T>G. The allelic frequencies of the mutations were varied, with the CC genotype predominating in SNP1, the GT hybrid in SNP2, and TG in SNP3. Statistical results showed no significant differences in most of the studied traits between the different genotypes, with a statistically significant superiority in total milk production observed for the GT genotype in SNP2.